Changes of postharvest quality in passion fruit (Passiflora edulis Sims) under modified atmosphere packaging conditions - P. Maniwara (2018)
The modified atmosphere packaging technique was explored in order to investigate the changes of passion fruit quality during low temperature storage. Three different types of packaging condition were used in this experiment. They were (i) P-UAP, a perforated low density polyethylene (LDPE), (ii) MAP-1, a LDPE with an oxygen transmission rate (OTR) of 14000-16000 cm3/m2bullet operatordaybullet operatoratm, and (iii) MAP-2, an ethylene absorber laminated LDPE with an OTR of 12000 cm3/m2bullet operatordaybullet operatoratm. Five fresh purple passion fruits (each fruit was about 100 g) were packaged in each type of packaging and then stored at 10±1°C, 79-84% RH. During storage, the headspace gas concentrations, physico-chemical quality and sensory acceptability were monitored. Oxygen concentration of headspace gas in MAP-1 and MAP-2 markedly decreased during 12 hours after packaging while carbon dioxide greatly increased. The gases in MAP-1 and MAP-2 reached equilibrium within 14 and 7 days, respectively. The passion fruit in all packaging conditions showed decreased presence of total soluble solids, titratable acidity and vitamin C content over the storage period. However, plastics MAP-1 and MAP-2 significantly reduced fresh weight loss and delayed fruit wrinkling. Pulp off-flavor was observed in the fruit stored in MAP-1 and MAP-2 wrapping, and this resulted in a lack of marketability. The MAP-2 plastic showed the best results in maintaining fruit quality, gas composition, and extension of storage life (up to 51 days).